Teaching and Learning Programming and Software Engineering via Interactive Gaming - Tillmann, Nikolai; Halleux, Jonathan "Peli" de; Xie, Tao; Gulwani, Sumit; Bishop, Judith (ICSE '13 Proceedings of the 2013 International Conference on Software Engineering, 2013)
Massive Open Online Courses (MOOCs) have recently gained high popularity among various universities and even in global societies. A critical factor for their success in teaching and learning effectiveness is assignment grading. Traditional ways of assignment grading are not scalable and do not give timely or interactive feedback to students. To address these issues, we present an interactive-gaming-based teaching and learning platform called Pex4Fun. Pex4Fun is a browser-based teaching and learning environment targeting teachers and students for introductory to advanced programming or software engineering courses. At the core of the platform is an automated grading engine based on symbolic execution. In Pex4Fun, teachers can create virtual classrooms, customize existing courses, and publish new learning material including learning games. Pex4Fun was released to the public in June 2010 and since then the number of attempts made by users to solve games has reached over one million. Our work on Pex4Fun illustrates that a sophisticated software engineering technique – automated test generation – can be successfully used to underpin automatic grading in an online programming system that can scale to hundreds of thousands of users.